PENGARUH PUPUK NPK PELANGI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) - Nikolaus Odiluda; Josina Irene Brigetha Hutiubessy (AGRICA, 2018)
The study aimed to determine the effect of NPK Pelangi fertilizer on the growth and yield of cucumber and its optimum dosage. This study uses a Randomized Block Design (RBD). The treatments are Po: Rainbow NPK Fertilizer 0 kg ha-1 (control); P1: NPK Pelangi Fertilizer 300 kg ha-1 = 150 gr plot-1; P2: Rainbow NPK fertilizer 600 kg ha-1 = 300 gr plot-1; P3: Rainbow NPK Fertilizer 900 kg ha-1 = 450 gr plot-1; P4: Rainbow NPK Fertilizer 1200 kg ha-1 = 600 gr plot-1. The results showed that NPK Pelangi fertilizer had a very significant effect on leaf average (11.89%), leaf area-1 (12.85%), number of fruit tan-1 (26.37%), fruit length tan-1 (4 , 42%), diameter of fruit tan-1 (8.77%), weight of fruit tan-1 (30.33%), weight of fruit ha-1 (30.33%). The optimum dose of NPK Pelangi fertilizer is 1,200 kg ha-1 because it provides optimal growth and yield on the number of leaves (15,13 strands) of leaf area-1 (420.69 cm²), number of fruit tan-1 (7.13 pieces), length of fruit tan-1 (17.21 cm), diameter of tan-1 fruit (15.13 mm), weight of fruit tan-1 (2492.75 grams), weight of fruit ha-1 (99.71 tons).